Word Creation in Speech of Animated Series Character “Masha and the Bear” - A. D. Rebrova; N. S. Gegelova (Научный диалог, 2023)
The features of children’s word creation in one of the series of the animated film “Masha and the Bear” are studied. The relevance of the study is due to the fact that the study of the language game on the example of the speech of children’s cartoon characters allows us to obtain new information about the features of children’s word creation in modern media products. It is shown that the authors of the animated series “Masha and the Bear” deliberately use a variety of game techniques to imitate children’s speech. A series is analyzed, which is devoted to playing out the features of the creative activity of children when they master the language. It is noted that the character Masha in this series uses spoonerisms and occasionalisms. Foreign translations of these means of expression into English, French, Spanish and Ukrainian are given. It is shown that not all unusual words that Masha creates are translated in foreign cartoons with exact equivalents. Some of them are replaced by the names of animals, the image of which is more often used in foreign culture. It is concluded that children’s word creation in media content has not been sufficiently studied, while it plays an important role both in reflecting the characteristics of children's speech and in shaping the creative thinking of young viewers.